The mystery of methylene blue and its role in managing post-cardiac surgery vasoplegic shock - Mohamed Elbayomi; Oliver Dewald; Presheet Pathare; Markus Kondruweit; Rene Tandler; Michael Weyand; Christian Heim (Annals of Medicine)
Background Vasoplegic syndrome is associated with high mortality. Methylene blue (MB) is a guanylate cyclase inhibitor that ameliorates this re-distributive type of shock. This study aims to investigate the outcome in patients who received MB early postoperatively.Methods 2753 patients who underwent cardiac surgery utilizing cardiopulmonary bypass at our institution in a time interval of two years were identified. The incidence of vasoplegic syndrome was 7.2% (n = 200). Pharmacy records identified 84 patients (group 1, MB group) who received methylene blue and 116 patients (group 2, Control group) who didn’t receive the drug. This single-center retrospective cohort study’s primary outcome was in-hospital mortality. Secondary outcomes were postoperative hemodialysis, serum lactate levels at 24 h postoperatively, and intensive care unit stay length in days.Results MB patients have a shorter ICU stay as compared to the control group (9 ± 8 days vs. 16 ± 6.9; p-value <.001). In the control group, postoperative hemodialysis was higher (20% in the MB group and 40% in the control group; p-value <.05). At 24 h post-op, the methylene blue group had reduced serum lactate levels (1.8 ± 1.2 vs. 4 ± 1.8 in the control group; p-value <.001). The methylene blue group had a decreased 24-hour norepinephrine dose (1.5 ± 1.2 vs. 2.8 ± 2 in the control group; p-value <.05). In-hospital mortality was not significantly different between the two groups (38% in the MB group vs. 43% in the control group).Conclusion Early postoperative administration of methylene blue in patients with vasoplegic syndrome shortens intensive care unit stay and contributes to less end-organ damage.